Where did all the unemployed go? Non-standard work in Germany after the Hartz reforms - Thomas Rothe; Klaus Wälde (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
The number of unemployed workers in Germany decreased dramatically from its peak in February 2005 at over 5.2 million to 3.6 million by 2008. At the same time, employment increased by 1.2 million. Most theoretical and empirical analyses of this episode assume that a worker leaving unemployment moves into full employment. We ask where the unemployed actually went. Using and merging two large micro data sets, we account for the decrease of unemployment by computing inflows and outflows between unemployment and 16 other labour market states. Direct flows between unemployment and full employment contributed for only less than 9 percent to the decline in unemployment. By contrast, more than 37 percent of the unemployed workers ended up in non-standard work. About 13 percent participated in labour market policy programmes and 28 percent retired. Following the unemployment cohort of February 2005 over time confirms the order of magnitude of our findings. – – Seit ihrem Höhepunkt im Februar 2005 sank die Arbeitslosigkeit in Deutschland innerhalb von drei Jahren von 5,2 Millionen auf 3,6 Millionen, während die Erwerbstätigkeit um 1,2 Millionen stieg. Die meisten theoretischen und empirischen Analysen gehen implizit davon aus, dass Arbeitslose im Wesentlichen in Vollzeit-Erwerbstätigkeit wechseln. Wir fragen wohin die Arbeitslosen tatsächlich gehen. Wir erklären den Rückgang der Arbeitslosigkeit, indem wir die Übergänge zwischen Arbeitslosigkeit und 16 anderen Erwerbsstatusarten anhand zweier großer Mikro-Datensätze berechnen. Es zeigt sich, dass direkte Übergänge zwischen Arbeitslosigkeit und Vollzeit-Erwerbstätigkeit nur knapp 9 Prozent zum Rückgang der Arbeitslosigkeit beitrugen. Dagegen wechselten mehr als 37 Prozent der Arbeitslosen in atypische Beschäftigungsverhältnisse. Weitere 13 Prozent nahmen an arbeitsmarktpolitischen Maßnahmen teil und 28 Prozent gingen in den Ruhestand. Wenn wir den Verbleib der Arbeitslosenkohorte vom Februar 2005 über die Zeit verfolgen, bestätigen sich diese Ergebnisse im Wesentlichen.
Keywords: J21; J62; J64; 330; non-standard work; empirical labour market flows with many states; Germany labour market reform; Hartz reforms